Lower-Limb Sensorimotor Deprivation-Related Brain Activation in Patients With Chronic Complete Spinal Cord Injury - Gao, Feng; Guo, Yun; Chu, Hongyu; Yu, Weiyong; Chen, Zhenbo; Chen, Liang; Li, Jun; Yang, Degang; Yang, Mingliang; Du, Liangjie; Li, Jianjun; Chan, Chetwyn C. H. (Frontiers in Neurology, 2020)
Brain reorganization have occurred after spinal cord injury(SCI), but it is unclear whether the changes is associated with the sensorimotor dysfunction. This study aims to investigate functional brain reorganization brought about by the loss of physical movement and sensory feedback in lower limbs in chronic SCI. Eleven paraplegia patients with SCI and thirteen healthy controls(HCs) were recruited. The experimental task used was a visuomotor imagery task requiring subjects to engage in visualization of repetitive tapping movements of the upper or lower limbs. Blood oxygen level-dependent (BOLD) signals were captured during the experimental tasks, along with the accuracy rate and the response time in the cognitive tests. The SCI patients performed worse in the Rey Auditory Verbal Learning Test and the Trail Making Test. SCI patients had a larger BOLD signal in the left lingual gyrus and right external globus pallidus (GPe) when imagining lower limb movements. For the upper limb task, SCI patients showed stronger BOLD signals than the HCs in extensive areas over the brain, including the bilateral precentral gyrus, bilateral inferior parietal gyrus, right GPe, right thalamus, left postcentral gyrus and right superior temporal gyrus. In contrast, the HCs displayed stronger BOLD signals in the medial frontal gyrus and anterior cingulate gyrus for both upper and lower limb tasks than the SCI patients. Our study provided imaging evidence for altered changes in brain function and worsened cognitive tests performance in SCI patients. These findings suggested possible compensatory strategies adopted by the SCI patients for the loss of sensorimotor function from the lower limbs when performing a limb imagery task.